Pengaruh Pengelasan SMAW dengan Variasi Elektroda E6013 dan E7016 terhadap Kekuatan Tarik dan Kekerasan pada Baja SS400 - Muhammad Arief Rosadi; Agus Suprihanto; FX. Arif Wahyudianto; Agus Hariyanto; Abdul Muis (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2026)
In today's era of globalization, the manufacturing industry is a key pillar of the global economy. Shielded Metal Arc Welding (SMAW) is a popular choice due to its relatively low cost. In this research, the material used was carbon SS 400 KS (Krakatau Steel). It was welded with E6013 and E7016 electrodes with a diameter of 3.2 millimeters. The material dimensions were 300 millimeters long, 100 millimeters wide, and 8 millimeters thick, consisting of four pairs (8 sheets). Tests used included tensile testing and hardness testing (Vickers procedure). The highest tensile strength using E6013+E6013 electrodes has an average of 364.37 MPa, the highest yield strength using E7016+E7016 electrodes has an average of 464.14 MPa and the highest hardness test using E7016+E6013 electrodes has an average value in the Welding Metal area of ​​206.90 kgf/mm², while the HAZ area is 172.78 kgf/mm², and the Base Metal area is 161.92 kgf/mm². Based on the results of research conducted on the mechanical properties of SMAW welding joints with variations of E 6013 and E 7016 electrodes, it can be concluded that both types of electrodes have different characteristics in producing weld quality.